Bone mineral density in elderly and senile women with knee and hip osteoarthritis - Yu. V. Averkieva; I. I. Grigorieva; T. A. Raskina (Современная ревматология)
Objective: to study bone mineral density (BMD) in elderly and senile women with knee and hip osteoarthritis (OA).Patients and methods. The investigation enrolled 124 women (mean age, 73.3±8.46 years) diagnosed with OA meeting the ACR diagnostic criteria. Lumbar spine (LI-IV) and femoral neck BMD values were determined; knee and hip X-ray in the frontal projection was carried out to assess the radiographic stage according to the Kellgren and Lawrence classification.Results and discussion. The overall incidence of osteoporosis (OP) and ostopenia in the study cohort was 28 and 41%, respectively. OP was diagnosed in 20% of women aged 60–74 years and in 38% of those aged 75–90 years (p<0.05); osteopenia was in 41 and 42%, respectively (p>0.05). In the age groups of 65–74 years and ≥75 years, women with stage III–IV hip OA had a significantly higher femoral neck BMD than those with Stage I–II (p<0.05). At the same time, the later radiographic stages of hip OA were associated with lower lumbar spine BMD (p<0.05). The patients of both age groups who had Stages III and IV knee OA had a significantly higher lumbar spine BMD than those with Stage I–II OA (p<0.05). The femoral neck BMD in patients with Stages I–II and III–IV knee OA was comparable in both age groups (p>0.05).Conclusion. The relationship between BMD and OA-related structural changes is contradictory and requires further investigation.